Development and Application of Methods for Determining Morphological Changes in the Umbilical Cord during Pregnancy Complicated by Fetoplacental Insufficiency (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The health of the unborn baby largely depends on how the placenta works, because it is this organ that provides it with the necessary nutrition and oxygen. During pregnancy, the mother and the fetus are so closely connected through the placenta that a complex complex called the "mother-placenta-fetus system" is formed. The placenta is what connects the mother to the child. This temporary organ is formed during pregnancy. With its villi, it is connected to the wall of the uterus on one side, and on the other side to the fetus through the umbilical cord.